Forecasting Sales: A Comprehensive Analysis of Forecasting Techniques for Sales Budget Determination - Ravitilova, Ravitilova; Amelia, Devi; Saputra, Ilham; Rinda, Rinda (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2023)
This research endeavors to employ sales forecasting techniques on historical sales data for the purpose of determining the sales budget. The application of forecasting is based on sales data from the preceding period, utilizing a descriptive qualitative method. The analysis employs the half-average trend method, generating an estimated sales figure for the upcoming period. This estimate serves as a reference for both inventory planning and the formulation of the sales budget. Within this research, the half-average trend method involves the selection of two X parameter values, namely 0.5 and 0. To determine the superior value, a calculation of SKF (Standard Error of Forecasting) is executed. The analysis results reveal that utilizing the value 0 yields an SKF value of 4,166.6, while the value 0.5 produces a lower SKF value of 3,941.6. This implies that the estimated sales number with the X value of 0.5 is smaller than that with the X value of 0. Conclusively, the application of the half-average trend method in this research provides sales estimates for the next three months, contributing valuable insights for effective planning and budgeting processes.